2016
DOI: 10.1371/journal.pone.0165416
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacies and Safety of Combined Therapy between Telbivudine Plus Adefovir and Lamivudine Plus Adefovir in Patients with Hepatitis B Virus Infection in Real-World Practice

Abstract: Background and AimChronic hepatitis B infection remains a significant health issue worldwide. This study evaluated the efficacy and safety of combined therapy using lamivudine plus adefovir (LAM+ADV) versus telbivudine plus adefovir (LdT+ADV) and the corresponding renal function change and safety.MethodsThis study enrolled a total of 171 patients (110 patients received LAM+ADV and 60 patients received LdT+ADV). We analyzed the changes in renal function using the estimated glomerular filtration rate (eGFR). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Few studies have examined the effect of L-dT and ADV combination treatment for LMV-resistant CHB. Lin et al reported that L-dT + ADV showed a reasonable virological response rate compared to LMV + ADV treatment (29). However, the study was not randomized and had limited participants.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the effect of L-dT and ADV combination treatment for LMV-resistant CHB. Lin et al reported that L-dT + ADV showed a reasonable virological response rate compared to LMV + ADV treatment (29). However, the study was not randomized and had limited participants.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, a previous study found that in the case of ADV-based combination therapy, adding on LdT was reported to result in better renal protection than adding on lamivudine or entecavir [ 31 ]. In other studies in which the strategy of adding on ADV or TDF was applied, combining either drug with LdT could still result in improved eGFR [ 32 , 33 ]. Our results were comparable with the results of those previous studies.…”
Section: Discussionmentioning
confidence: 99%